25th September: 19th Sunday after Pentecost - Cleugh, Hannah (The expository times, 2016)
The article reflects on the theme of trusting God based on the Biblical readings in Amos 6.1a and 4-7, Psalm 146, 1 Timothy 6.6-19 and Luke 16 for the 19th Sunday after Pentecost on September 25, 2016. Topics addressed include the role of Anglican bishop Lancelot Andrewes and Russian monastic reformer Sergei Radonezh in reforming the Church, the parable of Lazarus and Jesus' criticism of the Pharisees' hypocrisy.